Biginelli reaction – an effective method for the synthesis of dihydropyrimidine derivatives - Simurova, Natalia; Mayboroda, Elena (My University, 2017)
A brief review of the publications over the past 5 years devoted to the synthesis of 3,4-dihydropyrimidin-2(1H)-one derivatives using Biginelli reaction is presented. The impact of reaction conditions (solvents, catalysts) on the yield is discussed. New combinations of reagents enabling the synthesis of a wide range of 3,4-dihydropyrimidin-2(1H)-one derivatives with various functional groups are considered.
Keywords: реакція Біджінеллі; похідні дигідропіримідину; синтез; умови реакції; Biginelli reaction; dihydropyrimidine derivatives; synthesis; reaction conditions; кафедра харчової хімії